Neurocysticercosis in Pregnancy - Camille Webb; Mauricio La Rosa; Gayle Olson; Miguel Cabada (Thieme Medical Publishers, Inc., 2018)
The normal physiologic changes during pregnancy contribute to nutritional, metabolic, and immunologic adjustments, which can have an impact on the presentation of several diseases. New onset seizures during pregnancy and the postpartum can be attributed to several etiologies. Patient demographic data as well as personal and social histories are key in determining the etiology of new onset seizures. Neurocysticercosis (NCC), a commonly overlooked etiology, must be included in the differential diagnosis of patients with new onset seizures coming from NCC endemic areas. The diagnosis is based on a combination of clinical findings, exposure history, imaging, and serology. We present two cases of patients with NCC that became symptomatic during pregnancy or postpartum period. We will review the epidemiology, clinical manifestations, and management of NCC in pregnancy.